Analysis of Several Factors that Influence the Volume of Orange Imports in Indonesia - Saidah, Zumi; Yudha, Eka Purna; Supyandi, Dika (Universitas Galuh, 2025)
This study aims to analyze the impact of the Consumer Price Index (CPI), international prices, and import tariffs on the import volume of oranges in Indonesia. The increasing volume of orange imports in recent years indicates that external factors play a role in determining import levels. The variables examined in this study include CPI as an indicator of domestic purchasing power, international orange prices as a reflection of global market dynamics, and import tariffs as a government policy affecting international trade. The data used in this study is annual data from 2010 to 2023. The analysis method employed is multiple linear regression to observe the effects of each independent variable on the volume of orange imports. The results show that CPI has a positive and significant impact on the volume of orange imports, indicating that higher CPI levels lead to an increase in imports. International prices have a significant negative effect, implying that an increase in global orange prices reduces the import volume of oranges in Indonesia. Import tariffs also have a negative and significant impact on orange import volumes, meaning that higher import tariffs decrease the number of oranges imported. The multiple linear regression model has a coefficient of determination (R²) of 0.85, indicating that 85% of the variation in the orange import volume can be explained by these three independent variables. These findings highlight the importance of controlling import tariffs and monitoring international prices to effectively manage the volume of orange imports in Indonesia.